Effects of Hepatitis on Diabetic Profile, Renal Function, and Hematological Factors in HCV Positive Patients Diagnosed via Real-Time PCR - Batool, Tahira; Idrees, Tahira; Akbar, Rukhsar; Mutaqeen, Rabbia; Irshad, Asma (BioScientific Review, 2025)
Background. Hepatitis C virus (HCV) is a blood-borne infection that has spread all over the world. Around 10 million people in Pakistan are impacted by HCV, while over 58 million people worldwide have a chronic HCV infection. HCV is well known for its severe effects on the liver as well as its extra-hepatic manifestations. Objective. This study assessed the renal profile (urea and creatinine), hematological factors (Hb, HCT, MCV), and diabetic profile (blood glucose fasting, blood glucose random, and HbA1c) of HCV-positive patients confirmed by real-time PCR (RT-PCR). The main aim was to determine the impact of hepatitis infection. Methodology. This was a retrospective cohort study conducted on patients diagnosed as HCV-positive by using real-time PCR (RT-PCR). Their diabetic, renal, and hematological association with HCV was observed and analyzed by using SPSS 25. Results. Out of 296 HCV-positive patients, 174 (58.8%) were male and 122 (41.2%) were female, indicating that HCV was found to be more prevalent in male patients. There was no statistical association found between HbA1c and gender. However, there was found a significant association of blood glucose fasting and blood glucose random with gender. Renal and hematological profiles were also disturbed in HCV-infected individuals. Conclusion. Health professionals may benefit from this study by managing disrupted profiles more effectively and providing improved patient care. Additional research on the disrupted hematological, renal, and diabetic profiles may improve the treatment conditions for patients since these profiles revealed a variety of extra-hepatic symptoms in this study